Orbital lymphoma: Role of radiation - Yadav B; Sharma S (Indian Journal of Ophthalmology, 2009)
The purpose of this article is to review the literature for clinical presentation, treatment, outcome and complications of using radiotherapy for the treatment of orbital lymphoma. For this, MEDLINE, EMBASE, and the Cochrane Library were searched through January 2007 for published data on primary non-Hodgkin′s lymphoma (NHL) of the orbit. The search was conducted in all document types, using the following terms "Non-Hodgkin′s lymphoma, MALT (mucosa associated lymphoid tissue) and orbit". Data extracted were based on age, sex, therapeutic methods and outcome of treatment. When full articles were not available, abstracts were used as a source of information. Only those articles whose abstracts or full text were available in English were included in table. The review of reports of NHL of the orbit, in general, served as a source of information about its clinical behavior, treatment and overall prognosis. Fifty-six publications were identified, including six in languages other than English. There was no randomized trial. All the studies were retrospective. The studies were heterogeneous in patient number (3 to 112), histology, disease stage (IE to IV), radiotherapy doses used (4 to 53.8Gy), local control rates (65 to 100%), distant relapse rates (0 to 67%, from low grade to high grade) and five-year survival rates (33 to 100%). Three of the studies with a good number of patients also demonstrated clinical benefit with radiotherapy in terms of superior efficacy or less toxicity. Available data support the acceptance of radiotherapy as a standard therapeutic option in patients with low to intermediate grade orbital lymphoma. Toxicity of radiotherapy is mild if delivered precisely.